Analysis of Cost Realization Based on Budget as a Control Tool at CV. Achazia Tigris - Ichin Rante Allo; Agustinus Mantong; Yohanis Lotong Ta’dung (LP2M IAIN Palopo, 2025)
This study aims to analyze and determine the cost budget and its realization as a cost control tool at CV Achazia Tigris. Using quantitative descriptive method with a research approach used to describe something factually and accurately using numerical data by comparing the budget and cost realization using analysis of variance as a tool to determine the difference between budget and cost realization and using documentation techniques by analyzing company documents such as project cost budget plans. The results of the analysis of CV. Achazia Tigris in implementing this project, preparing a project cost budget as a form of project cost planning without knowing the unexpected risks that occur during the implementation of the new classroom construction project. This states that the cost budget function has not functioned properly as a control tool because there are still unfavorable differences (unfavorable) for the company. This research is important to analyze unexpected risks that occur to minimize losses that may occur so that no losses occur in the implementation of the next project.